The ESG Paradox Revisited: Integration of Environmental Justice Criteria - Ballan, Barbara (Columbia Journal of Environmental Law, 2026)
In the age of information and climate disruption, businesses must navigate the perils of environmental degradation and deregulation and the unfolding of an informational and technological revolution. Under this context, companies can utilize innovative reporting frameworks to measure, assess, and disclose their environmental and social impacts, particularly on communities that have been historically and disproportionately affected by corporate decision-making. This Article explores the paradox that lies at the intersection of two trending acronyms: Environmental, Social, and Governance (ESG) reporting, defined as a metric-driven approach to achieve corporate accountability and which can be imposed mandatorily by public law or voluntarily through Private Environmental Governance (PEG); and Environmental Justice (EJ), a social movement that denounces the unfair distribution of environmental impacts on vulnerable communities, and which has evolved into policies and sophisticated metrics and frameworks to assess inequalities in environmental harms caused by private and public decision-making. Due to the current political attacks on environmental policies, mandatory ESG remains improbable. Thus, this Article analyzes how businesses are voluntarily disclosing environmental and social impacts. There are compelling reasons that justify the integration of EJ risks into sustainability reporting, including material climate-related risks, investor and consumer preferences, and achieving long-term corporate value. Corporate governance, related to corporate design, fiduciary duties, and the role of management, can adapt to integrate EJ considerations, redefining the rules and practices that shape shareholder-management relationships. This Article argues that EJ risks and opportunities should be material for businesses to disclose. ESG reporting that integrates environmental justice objectives can also promote the long-term viability of a business. In the absence of public regulation, the integration of EJ into voluntary ESG frameworks offers an innovative interim solution for advancing environmental stewardship and responding to the urgent challenges of our time.